Study of a new neutron dosimeter incorporating RPL detectors. (December 2015) - Nourreddine, A.; Salem, Y.O.; Nachab, A.; Roy, C.
Abstract: We characterize a passive dosimeter incorporating RadioPhotoLuminescent (RPL) detectors capable of measuring both fast and thermal neutrons for personal dosimetry. These neutrons can be detected in a mixed n-γ field with appropriate converters. Monte Carlo simulations with MCNPX helped with the geometrical conception of the dosimeter and the choice of materials. The responses of the RPL dosimeter are linear in H p (10) with detection limits of 1.83 mSv for fast neutrons and 0.19 mSv for thermal neutrons. The angular dependencies are satisfactory according to the ISO 21909 norm. A calibration factor of (9.5 ± 0.5) × 10 −2 mSv cm 2 /RPL intensity was obtained for the fast neutrons of the IPHC's 241 Am–Be calibrator. The factor was (9.7 ± 0.3) × 10 −3 mSv cm 2 /RPL intensity for thermalized neutrons.